Patterns of dairy manure management in China - Chenyan, Li; Wei, Qiao; Melse, Roland W.; Lujun, Li; Buisonjé, Fridtjof E. de; Yajing, Wang; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The dairy industry in China is rapidly developing, particularly in terms of the upscaling of dairy farms. However, nutrient-rich manure brings challenges to the sustainability of the dairy industry. This study investigated and reviewed the patterns of dairy manure management in China, and the results indicate that dairy manure could be used as an organic fertilizer because of its high organic nutrient content and low metal content. However, legislation prohibits the application of untreated (raw) dairy manure. An existing technology for handling animal slurry is the separation into a liquid and a solid manure fraction. The solid fraction can be used as compost and bedding materials, and it has limited environmental risk. However, the emissions from the storage of liquid manure need further attention. The cycle of manure production, collection, transportation, separation and storage can only be closed if the nutrients are eventually applied to grass and arable land according to crop needs. Therefore, distribution of knowledge on nutrient levels, crop needs and nutrient management plans, supported by legislation on maximum application standards, is needed. In this way, an environmentally friendly development of dairy manure management might be possible.Keywords: dairy manure, manure handling pattern, legislation, nutrient recycling, emissionsDOI: 10.3965/j.ijabe.20171003.3048Citation: Li C Y, Qiao W, Melse R W, Li L J, de Buisonjé F E, Wang Y J, et al. Patterns of dairy manure management in China. Int J Agric & Biol Eng, 2017; 10(3): 227–236.